2021
DOI: 10.1111/pai.13602
|View full text |Cite
|
Sign up to set email alerts
|

Association of phthalate exposure and airway dysfunction with mediation by serum periostin

Abstract: Previous studies reported that exposures to environmental pollutants are responsible for the increasing prevalence of allergic diseases. 1,2 Here, we focused on phthalates, a group of chemicals commonly used as plasticizers that commonly have higher concentrations in children than adults. 3 Phthalates can have adverse effects on the respiratory and immunological systems. Epidemiological studies reported positive associations between indicators of phthalate exposure and risk of asthma, and allergic diseases. 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Epidemiological studies suggested that exposure to phthalates was correlated with increased airway inflammation. 25 Phthalates elevated levels of oxidative stress and accelerated the recruitment and activation of lung neutrophils, which contribute to pulmonary inflammation. 26 Oxidative stress is the result of an imbalance of ROS and antioxidants in the body and plays a crucial role in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggested that exposure to phthalates was correlated with increased airway inflammation. 25 Phthalates elevated levels of oxidative stress and accelerated the recruitment and activation of lung neutrophils, which contribute to pulmonary inflammation. 26 Oxidative stress is the result of an imbalance of ROS and antioxidants in the body and plays a crucial role in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Baek et al have documented that exposure to phthalates is associated with airway dysfunction in childhood, and this effect was partially attributable to increased serum periostin levels. 6 With regard to the association between the genes and environment, Theodorou et al 7 have investigated the role of mitogen-activated protein kinase (MAPK) pathway in 232 children who were selected from two cross-sectional cohorts and one birth cohort study. They have isolated peripheral blood mononuclear cells (PBMCs) from children with asthma along with healthy controls and stimulated them with farm-dust extracts or lipopolysaccharide.…”
Section: Of 4 |mentioning
confidence: 99%
“…The authors have concluded that the levels of cadmium in cord blood were associated with greater risk of asthma at the age of 8. Baek et al have documented that exposure to phthalates is associated with airway dysfunction in childhood, and this effect was partially attributable to increased serum periostin levels 6 . With regard to the association between the genes and environment, Theodorou et al 7 have investigated the role of mitogen‐activated protein kinase (MAPK) pathway in 232 children who were selected from two cross‐sectional cohorts and one birth cohort study.…”
mentioning
confidence: 99%
“…The authors have concluded that the levels of cadmium in cord blood were associated with greater risk of asthma at the age of 8. Baek et al have documented that exposure to phthalates are associated with airway dysfunction in childhood and this effect was partially attributable to increased serum periostin levels (6). Regarding the association between the genes and environment, Theodorou et al (7) have investigated the role of mitogen-activated protein kinase (MAPK) pathway in 232 children who were selected from two cross-sectional cohorts and one birth cohort study.…”
mentioning
confidence: 99%